Arboviruses in birds captured in Slovakia - Ernek, E; Kozuch, O; Nosek, J; Teplan, J; Folk, C (Journal of hygiene, epidemiology, microbiology, and immunology, 1977)
Virus neutralizing (VN) antibodies against Sindbis, tick-borne encephalitis (TBE), West Nile (WN), Tahyna and Calovo viruses were found in birds captured in Slovakia. In parallel, Sindbis, TBE and WN viruses were isolated from the blood, brain and liver of migrating birds.
Keywords: virus západního Nilu; virus Bunyamwera; Arboviruses; viry kalifornské encefalitidy; arboviry; Bunyamwera virus; Antibodies, Viral; viry klíšťové encefalitidy; Sindbis Virus; ptáci; Birds; Animals; Encephalitis Viruses, Tick-Borne; protilátky virové; West Nile virus; Encephalitis Virus, California; virus Sindbis; zvířata